2021
DOI: 10.3390/bios11100370
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Part-Per-Billion Level Sensing of Fentanyl Residues from Wastewater Using Portable Surface-Enhanced Raman Scattering Sensing

Abstract: Detection of illicit drug residues from wastewater provides a new route toward community-level assessment of drug abuse that is critical to public health. However, traditional chemistry analytical tools such as high-performance liquid chromatography in tandem with mass spectrometry (HPLC-MS) cannot meet the large-scale testing requirement in terms of cost, promptness, and convenience of use. In this article, we demonstrated ultra-sensitive and portable surface-enhanced Raman scattering sensing (SERS) of fentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…[ 27–34 ] Additional studies have reported the SERS detection of a wide range of abused drugs in solution, [ 35 ] such as cocaine, [ 36 ] amphetamines, [ 37,38 ] ring substituted amphetamines, [ 39–41 ] bath salts, [ 42,43 ] opioids [ 21,35,44–48 ] including drug mixtures laced with fentanyl, [ 49–53 ] hallucinogens, [ 27,54,55 ] marijuana active ingredients, [ 35 ] and other prescription and over the counter drugs. [ 35 ] Sensitivity at low detection limits is possible even at sub‐nanogram per milliliter levels, as has been observed for fentanyl in wastewater [ 11 ] and reported in aqueous solution. [ 21 ] Most of the reported drug studies with SERS of biofluids have been performed in urine or simulated urine.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[ 27–34 ] Additional studies have reported the SERS detection of a wide range of abused drugs in solution, [ 35 ] such as cocaine, [ 36 ] amphetamines, [ 37,38 ] ring substituted amphetamines, [ 39–41 ] bath salts, [ 42,43 ] opioids [ 21,35,44–48 ] including drug mixtures laced with fentanyl, [ 49–53 ] hallucinogens, [ 27,54,55 ] marijuana active ingredients, [ 35 ] and other prescription and over the counter drugs. [ 35 ] Sensitivity at low detection limits is possible even at sub‐nanogram per milliliter levels, as has been observed for fentanyl in wastewater [ 11 ] and reported in aqueous solution. [ 21 ] Most of the reported drug studies with SERS of biofluids have been performed in urine or simulated urine.…”
Section: Introductionmentioning
confidence: 89%
“…One technology that offers great promise in overcoming such limitations is surface-enhanced Raman spectroscopy (SERS). SERS is versatile in its use and application and offers the ability to detect various drugs of concern at low concentration levels directly from surfaces, [9] as trace components in tablets or powders, [10] in wastewater, [11] and in biofluids, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] including saliva. [27][28][29][30][31][32][33][34] Additional studies have reported the SERS detection of a wide range of abused drugs in solution, [35] such as cocaine, [36] amphetamines, [37,38] ring substituted amphetamines, [39][40][41] bath salts, [42,43] opioids [21,35,[44][45][46][47][48] including drug mixtures laced with fentanyl, [49][50][51]…”
mentioning
confidence: 99%
“…Functionalization of the DE substrates was achieved using an in situ growth protocol previously optimized and published by our group [ 24 , 25 , 26 ]. Briefly, the DE coated substrates were soaked in a 1:1 solution of SnCl 2 and HCl (20 mM) for 30 min to allow effective binding of Sn 2+ ions on the silica rich diatom skeleton.…”
Section: Methodsmentioning
confidence: 99%
“…The use of SERS for analyzing drug analytes has become quite popular. In fact, the investigation of many drugs of abuse has been explored with SERS including amphetamines, MDMA, and amphetamine-like substances (Bell et al, 2000;Sägmüller et al, 2001;Faulds et al, 2002); barbiturates (Farquharson and Lee, 2000); mephedrone (Mabbott et al, 2013); and other types of drugs including cocaine, morphine, hydrocodone, fentanyl, codeine, diazepam, and fentanyl analogs (Farquharson et al, 2011;Rana et al, 2011;Leonard et al, 2017;Haddad et al, 2018;Shende et al, 2019b;Wang et al, 2019, Smith et al, 2021Wang H. et al, 2021;Wang L. et al, 2021;Wilson et al, 2021;Zhang et al, 2021). The use of SERS has also enabled the analysis of these drug analytes in toxicological specimens such as urine, saliva, and blood (Inscore et al, 2011;Andreou et al, 2013;D'Elia et al, 2018;Shende et al, 2019a;Sivashanmugan et al, 2019;Han et al, 2021).…”
Section: Introductionmentioning
confidence: 99%